2021
DOI: 10.1099/mic.0.001047
|View full text |Cite
|
Sign up to set email alerts
|

The ARC2 response in Streptomcyes coelicolor requires the global regulatory genes afsR and afsS

Abstract: ARC2 is a synthetic compound, related in structure and mechanism to the antibiotic triclosan, that activates the production of many specialized metabolites in the Streptomyces genus of bacteria. In this work, we demonstrate that the addition of ARC2 to Streptomyces coelicolor cultures results in considerable alterations in overall gene e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Interestingly, some SARPs, such as NosP in S. actuosus, can also respond to secondary metabolites and their intermediates (Li et al, 2018). Recently, the global regulator AfsR in S. coelicolor was shown to play an important role in the effect of the artificial elicitor ARC2 (Calvelo et al, 2021). This suggested that some signaling compounds were probably needed for the activation effect of AfsR.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, some SARPs, such as NosP in S. actuosus, can also respond to secondary metabolites and their intermediates (Li et al, 2018). Recently, the global regulator AfsR in S. coelicolor was shown to play an important role in the effect of the artificial elicitor ARC2 (Calvelo et al, 2021). This suggested that some signaling compounds were probably needed for the activation effect of AfsR.…”
Section: Discussionmentioning
confidence: 99%
“…This helps to explain the difference in NP induction observed between ARC2 and ARC6. More recently, Nodwell and co-workers delved deeper into the mechanism of ARC2 activation (Calvelo et al, 2021 ). To explore this, RNA-seq analysis of S. coelicolor treated with ARC2 was performed.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is likely that ARC2 induction of NPs is through activation of AfsS via a global stress response (Fig. 4A–B ) (Calvelo et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%